Analysis of Teacher Limitations in Using Thematic Learning Media at SD Negeri 101771 Tembung - Ayu Widya Ningsih; Handini Avantika Hasibuan; Rahmi Khairani Ritonga; Suhail Anshari; Laurensia M. Perangin Angin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Education is considered as one way to improve the quality, dignity and human dignity. Efforts to improve the quality of education are carried out so that national education goals can be achieved. The national education system can be realized, so there needs to be good cooperation from all learning components that are interconnected so that they are suitable for their purposes where the learning components consist of: curriculum, teachers, students, methods, media, and evaluation. The purpose of this study was to find out the causes of teacher limitations in using thematic learning media at SD Negeri 101771 Tembung. This research was conducted at SD Negeri 101771 Tembung. This research is a qualitative descriptive study which describes the Analysis of Limitations of Teachers in Using Thematic Learning Media at SD Negeri 101771 Tembung. The method used is interviews and questionnaires as a source of primary data and secondary data. From the research carried out, it was found that in the analysis of the use of Thematic learning media at SDN 101771, teachers still have limitations. Education requires teachers (teachers) who are able to create a conducive and more interesting atmosphere. Teachers still think that using learning media really requires time and money. Teachers also feel less interested in using learning media. Under these conditions, the teacher must not only provide the existing media or allow the limitations of the media to remain.